STUDIES FACILITATION ACQUISITION OF BASIC SCIENCE PROCESS SKILLS ON THE 4 GRADE STUDENTS MADRASAH TSANAWIYAH (MI) NW KERUMUT - Laras Firdaus; Hunaepi Hunaepi (Bioscientist : Jurnal Ilmiah Biologi, 2016)
ABSTRACT: Elementary school (ES) or Madrasah Ibtida'iyah (MI) is an essential part in the Indonesian education system, especially when viewed from a global perspective, the basic education aims to prepare the young generation to be able to adapt to the demands of the era. To support this, then Indonesia must be flexible to adapt, both in the content of the curriculum, as well as learning paradigm. A change of paradigm (paradigm shift) the emphasis on active engagement in the learning process (active consumer). That learning is none other than to help students acquire knowledge or understanding based on the integration of knowledge/understanding itself with science process skills (SPS). Science process skills (SPS) is identical to the behavior of scientists (scientists), so the SPS is recognized by the world as a way to acquire and knowledge development.